Analisis Semiotika Representasi Kepribadian Karakter Pada Series Anime Horimiya - Syaikh Rezon Satria Perdana; Muadz, Muadz (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2025)
The Horimiya anime series tells about the lives of Izumi Miyamura and Kyouko Hori as the main characters. The personalities of the two characters are in contrast to life at school. This study aims to determine the personality of the main characters of the Horimiya anime series, Izumi Miyamura and Kyouko Hori. This research is qualitative with John Fiske's semiotic approach, the data used is the Horimiya anime series and other literature that supports the research. The data collection technique was carried out by watching and recording every scene related to the research theme and then analyzed with the three main fields of study of semiotics Level of Reality, Level of Representation, and Level of Ideology by John Fiske.